Comparative Evaluation of the Increase in Enamel Hardness Post-External Bleaching after Using Casein Phosphopeptide Amorphous Calcium Phosphate Fluoride (CPP-ACPF) and 5% Sodium Fluoride (NaF) Remineralizing Agents - Irmaleny, Irmaleny; Hidayat, Opik Taofik; Yolanda, Yolanda; Tobing, Elisabeth Lumban (European Journal of Dentistry, 2023)
Objective The purpose of this study was to analyze the increase in enamel hardness post-external bleaching after remineralized with casein phosphopeptide amorphous calcium phosphate fluoride (CPP-ACPF) and 5% sodium fluoride (NaF) and the difference in increased enamel hardness between CPP-ACPF and NaF materials.Materials and Methods The study was true experimental in vitro using 30 samples of mandibular premolars. All samples were bleached using 40% hydrogen peroxide. The samples were divided into three groups of 10 samples each; group I as a control without application of remineralization material, group II was given an application of CPP-ACPF (GC Tooth Mousse Plus: GC Europe, Lot #201130B), and group III was given an application of 5% NaF (Clinpro White Varnish: 3M ESPE, Lot #NA62322) Then the entire samples were stored in artificial saliva. The hardness of the samples was measured using a Vickers hardness tester before bleaching, after bleaching, and after remineralization for 7, 14, and 21 days.Statistical Analysis Analysis of the data used was an analysis of variance test to assess differences in the increase in enamel hardness between groups and paired t-tests and to determine differences in enamel hardness in each group.Results This study showed that there was an increase in the enamel hardness after bleaching which was remineralized with CPP-ACPF and 5% NaF. There was a difference in the increased enamel hardness between teeth remineralized with CPP-ACPF and 5% NaF. The enamel hardness of CPP-ACPF was higher compared with 5% NaF after remineralization of 7, 14, and 21 days.Conclusion There was an increase in the enamel hardness after external bleaching that was remineralized with CPP-ACPF and 5% sodium fluoride (NaF). There was a difference in the increased enamel hardness between teeth remineralized with CPP-ACPF and 5% sodium fluoride (NaF). CPP-ACPF showed a higher enamel hardness value than 5% NaF.
Keywords: bleaching; enamel hardness; CPP-ACPF; 5% NaF; remineralization